Storybook Read-Alouds to Enhance Students’ Comprehension Skills in ESL Classrooms: A Case Study - Omar, Ainon; Saufi, Maizatulliza Mohd. (Dinamika Ilmu, 2015)
The effectiveness of using storybooks during read-alouds to develop children’s comprehension skills as well as in understanding the story has been widely studied. The reading aloud strategy has also been proven through numerous researches to be the most highly recommended activity for encouraging language and literacy. The study identified the comprehension strategies used by the teachers during their read-aloud sessions, matched teachers’ current practices using the comprehension strategies to the identified practices for the approach, and obtained the teachers’ perceptions of their current practices of the comprehension strategies during reading aloud in their English language classrooms. The teachers’ comprehension strategies were matched with a research-based strategy for comprehending texts during read-alouds proposed by Whitehurst et al (1994). Three primary school English language teachers teaching in the rural schools participated in this study. Qualitative research methods were used in this study. Primary data was obtained through observations using an observation protocol; while secondary data was obtained through interviews from teachers. Findings from the study revealed that the three teachers employed a few of the comprehension strategies that were proposed by researchers in the field. The findings also indicate that the teachers utilized only the strategies that they thought were relevant to their teaching context and as such, proposed the need to provide teachers with knowledge on the best practices for conducting reading aloud to develop ESL students’ comprehension skills